Isochronous creep rupture curves - ROGALSKA, E. (Engineering Transactions, 1990)
Isochronous creep rupture curves for damaged materials in the plane state of stress are investigated. The creep rupture criterion proposed by Litewka [6, 8] in terms of damage evolution equation and yield criterion were used. The isochronous curves of Nimonic 80A show that even for the same material limit curves are varying and their shape depends on the load level.